Strengthening education, extension and training to accelerate climate resilience and low carbon development in the agriculture sector - Ministry of Agriculture, Livestock, Fisheries and Cooperatives, Kenya (2020)
The dynamic nature of climate and its impacts on agriculture is rendering most of the existing adaptation and coping strategies unsupportive in many regions. Recent studies on economic sectors (including agriculture) across institutions and 24 counties have established the following: a widened gap between skills possessed by youth and those required by the job market; inadequate technical skills and knowledge on climate change and climate-smart technologies by the extension service providers; climate change has not been adequately integrated into Kenya’s formal agricultural education, extension and training systems such as the Kenya School of Agriculture (KSA), Agricultural Technology Development Centres (ATDCs), Agricultural Training Centres (ATCs) and Agriculture Technical Vocational Education and Training (ATVET); the existing policies and strategies for capacity building for the agriculture sector have limited provisions for promoting climate resilient and low carbon development solutions. These calls for integration of climate change into the formal education, extension and training systems; equipping the training institutions to facilitate adoption of climate-smart innovations; capacity building of the extension service providers to enhance utilization and adaptation of the appropriate support agricultural technologies, innovations and climate-smart farming practices.